1966
DOI: 10.1063/1.1728033
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Oxygen with Hot Tungsten

Abstract: The reaction of oxygen at a polycrystalline tungsten surface has been studied over a temperature range from 1300° to 2450°K and for oxygen pressures from ∼10−5 to ∼10−8 torr. A mass spectrometer was used to measure the oxygen pressure. In determining absolute pressures care was taken to avoid errors which may arise due to spurious currents in a Bayard—Alpert ion gauge. The efficiency of removal of carbon impurity from tungsten, by heating in oxygen, was determined. After obtaining a low carbon content, the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1968
1968
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…21 Redhead also showed that the use of a simple modulator electrode in a Bayard-Alpert gauge can permit both the detection of such errors and their correction, 20 though in at least one instance modulator readings were only valid when the pressure reached a steady state. 10 In measurement of pressure changes, the data of Fig. 2 show the slow response to a pressure measured by the ion gauge as compared to the mass spectrometer, but good agreement at equilibrium.…”
Section: Serious Perturbation Of the Gas Composition In A System Can mentioning
confidence: 84%
See 3 more Smart Citations
“…21 Redhead also showed that the use of a simple modulator electrode in a Bayard-Alpert gauge can permit both the detection of such errors and their correction, 20 though in at least one instance modulator readings were only valid when the pressure reached a steady state. 10 In measurement of pressure changes, the data of Fig. 2 show the slow response to a pressure measured by the ion gauge as compared to the mass spectrometer, but good agreement at equilibrium.…”
Section: Serious Perturbation Of the Gas Composition In A System Can mentioning
confidence: 84%
“…As the temperature increases above ϳ1650 K atomic oxygen production starts and by 2000 K is the predominant species. 10 Atomic oxygen may recombine at surfaces within the system, resulting in no net pumping, but it is also very reactive and will react with some surfaces in the vacuum system, leading either to a pumping effect, or to the generation of gaseous impurities ͑which is discussed later͒. The effective pumping simply depends upon the materials present in a system.…”
Section: B Pumping By the Gauge As A Consequence Of Reactions At Thementioning
confidence: 99%
See 2 more Smart Citations
“…These carbon species are emitted by the tungsten filament of the QMS. 16,17 We therefore have to consider the effect of C 2 O ϩ because we used a small amount of oxygen in the etching gas to reduce the etching rate of the SiO 2 mask. Figure 3 shows the intensities of the M /eϭ12, 28, 40, and 44 signals as a function of the oxygen concentration in SF 6 -O 2 with the plasma off.…”
Section: A Qms and Oes Measurement During Etchingmentioning
confidence: 99%